The world’s first Latin translation of the essay by Pseudo-Aristoteles Peri tw=n a)retw=n kai kakiw=n by Szymon Grynaeus, a professor at the University of Basel, from the collection of the Copernicus Library in Toruń - Dreikopel, Tomasz (Folia Toruniensia, 2021)
The study concerns the world’s first Latin translation of the essay On Virtues and Vices, preserved under the name of Aristotle, which was made in 1539 by Simon Grynaeus, then a professor at the University of Basel. In addition to the information about the author of the translation and linguistic comments, the study mentioned above also includes a spelling, punctuation, and editorial revision of Grynaeus’s translation prepared based on the edition that appeared in print in 1593 in Frankfurt and is in the collections of the Nicolaus Copernicus Public Provincial Library in Toruń.